Implementasi Pendidikan Karakter dan Moderasi Beragama di SDN Sokowaten Baru sebagai Sekolah Piloting Moderasi Beragama - Muhamad Hadli Alfurqon; Wasith Achadi; Muqowim Muqowim (ALSYS, 2026)
This study was motivated by the limited number of investigations on the implementation of religious moderation in primary schools, despite its significant impact on character formation and interreligious harmony among students. The study aimed to analyze the implementation of character education and religious moderation at SDN Sokowaten Baru as a piloting school for religious moderation. A descriptive qualitative method was employed, with the principal serving as the key informant selected through purposive sampling. Data were collected through in-depth interviews and analyzed using Miles and Huberman’s thematic analysis model. The findings show that SDN Sokowaten Baru has successfully implemented religious moderation through various programs, such as multireligious morning SOPs, inclusive Friday worship activities, participatory celebrations of religious holidays, and the integration of moderation values into classroom instruction. With a student body of 387 learners from diverse religious backgrounds (Islam, Protestant Christianity, Catholicism, and Hinduism), the school has achieved substantial success in reducing religion-based bullying, enhancing mutual respect, and strengthening understanding of diversity. The study concludes that key success factors include the principal’s visionary leadership, support from community and religious leaders, the availability of religious education teachers for each faith, and structured programs accompanied by continuous evaluation. The implications of this research include enriching the literature on religious moderation education at the primary school level, providing policy recommendations for the government to supply adequate religious teachers and worship facilities, and offering a contextual model for other schools to replicate. In addition, the study opens avenues for further research on the long-term impact of religious moderation programs on students’ attitudes and behaviour.